Libraries in Spain in 2011 - Hernández-Sánchez, Hilario; Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2012)
To know our libraries is also to know the status of our profession and our society. Thus, we draw on various data sources to describe and analyze the library scene in 2011 with the intention of determining their status. Access to library services, collections, professionals, expenses (and lack of expenditures), technologies, use of libraries, news about library legislation and the new political context are addressed.